2021
DOI: 10.3389/fnhum.2021.667035
|View full text |Cite
|
Sign up to set email alerts
|

Global Variability in Deep Brain Stimulation Practices for Parkinson’s Disease

Abstract: IntroductionDeep brain stimulation (DBS) has become a standard treatment option for select patients with Parkinson’s disease (PD). The selection process and surgical procedures employed have, to date, not been standardized.MethodsA comprehensive 58-question web-based survey was developed with a focus on DBS referral practices and peri-operative management. The survey was distributed to the Parkinson’s Foundation Centers of Excellence, members of the International Parkinson’s Disease and Movement Disorders Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, it is worth noting that none of these programs is specifically tailored to the unique challenges posed by DBS treatment. A specific educational program has been developed by surgical teams in France (ParkEduStim), which might help to align patient expectations with potential results from surgery [47, 53]. There remains a clear need for developing and implementing future programs specifically designed to address the unique challenges CGs face in the context of DBS treatment, informed by CB‐related evidence.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that none of these programs is specifically tailored to the unique challenges posed by DBS treatment. A specific educational program has been developed by surgical teams in France (ParkEduStim), which might help to align patient expectations with potential results from surgery [47, 53]. There remains a clear need for developing and implementing future programs specifically designed to address the unique challenges CGs face in the context of DBS treatment, informed by CB‐related evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Ruralized and non-Western under-resourced clinics would benefit greatly from this simple approach, as it is interpretable with minimal training. Thus, this methodology could augment accessibility and success of diagnostic and therapeutic approaches for individuals experiencing neurodegenerative, neuromuscular, or alike disorders [ 33 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that markerless tracking tools are a promising method for tracking kinematics in the OR and aiding in optimal DBS placement. This tool is particularly lucrative for under-resourced clinics; an investigation of non-Western deep-brain stimulation centers often in underdeveloped countries revealed that in some clinics, decisions on DBS candidacy and placement did not include a movement disorders neurologist (10.4%) or did not involve a committee whatsoever (53.5%) [ 46 ]. 33% of clinics did not employ a neurologist for DBS programming and 69% reported underutilization of DBS due to poor clinician knowledge [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, single-centre PSM analysis will be sensitive to targeting protocol and might produce a higher rate of false negatives in out-of-sample validation. Mahajan et al, [179] showed large global variability of the DBS practice in PD patients, which further indicated the importance of multi-center analysis. Boutet et al, [177] showed a high PSM-based prediction rate for PD sub-symptoms using in-sample validation (92-100%) and external clinic validation dataset (96-100%).…”
Section: Predicting Clinical Effectmentioning
confidence: 99%